2011
DOI: 10.1002/col.20714
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of an adjustment task to set preferred colour of ambient illumination

Abstract: An experiment was carried out to examine the method of adjustment when determining user preferences for the colour appearance of ambient lighting. A booth was lit using luminaires containing an array of white and coloured light emitting diodes (LEDs), allowing continuous variation of correlated colour temperature (CCT) between 2736 and 4014 K. It was predicted that the preferred CCT would be influenced by the available stimulus range, the anchor (initial setting before adjustment), adaptation time before onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…77 These studies also investigated anchors, the setting of the variable stimulus immediately before adjustment by the test participant, and these were set near the bottom, middle and top of the stimulus ranges. 24,77 The results demonstrated that final settings were influenced by the anchor, with low anchors leading to low estimates of preference and high anchors lead to high estimates. Such conservatism in adjustment is a common psychological tendency to adjust insufficiently and is manifest in a variety of sensory responses.…”
Section: Fotios and Chealmentioning
confidence: 99%
See 1 more Smart Citation
“…77 These studies also investigated anchors, the setting of the variable stimulus immediately before adjustment by the test participant, and these were set near the bottom, middle and top of the stimulus ranges. 24,77 The results demonstrated that final settings were influenced by the anchor, with low anchors leading to low estimates of preference and high anchors lead to high estimates. Such conservatism in adjustment is a common psychological tendency to adjust insufficiently and is manifest in a variety of sensory responses.…”
Section: Fotios and Chealmentioning
confidence: 99%
“…If the relationship between control setting and illuminance is linear, a mid-range anchor is appropriate to estimate preferences within ranges; 77 if the relationship is non-linear, then low and high anchors should be used in successive trials and the mean illuminance of these trials be used to give an estimate of preference for each test participant within the available range. Presentation order: The sequence of lamps, stimulus ranges and anchors is randomised or counterbalanced.…”
Section: Fotios and Chealmentioning
confidence: 99%
“…The average preferred CCT was 4151 K. The initial CCT that the subjects were exposed prior to adjustment varied between 3000 K, 4500 K and 6000 K. There were indications that the CCT preference leaned towards the initial setting, as was found also in [108], but the correlation between initial setting and user preference was just below statistical significance.…”
Section: User Adjusted Illuminance Level and Cct Preferencesmentioning
confidence: 66%
“…CCT 6000 K was considered less pleasant than 4500 K and 3000 K, but in other evaluated terms the results revealed no visible differences between CCTs. When the subjects were given control over CCT, the preferred CCT was on average around 4150 K. In a previous study [108] it was found that the initial CCT in a room affects the preferred CCT of the subjects. This was also found in the user tests [IV].…”
Section: Discussion and Analysismentioning
confidence: 96%
“…Actualmente un valor aproximado del CRI se encuentra disponible en la información técnica que entregan los fabricantes de luminarias. Adicionalmente se han realizado trabajos para determinar la respuesta de usuarios a cambios realizados en ambientes controlados donde se varia el CCT y el CRI (Logadóttir et al, 2013) y se evalúa su nivel de aceptación.…”
Section: Introductionunclassified